INSTALLATION OF A 10X100 WP SOLAR POWER PLANT AT AL-IKHLAS ORPHAN BOARDING SCHOOL, SINGOSARI DISTRICT, MALANG REGENCY - Hidayat, Mohammad Noor; Heryanto, Irwan; Eryk, Eryk; Saputra, Masramdhani; Santoso, Asfari Hariz; Harijanto, Priya Surya; Asrori, Asrori (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Solar power plants are efficient and environmentally friendly sources of renewable energy. Previously, a solar power plant with a capacity of 6 x 100 Wp had been installed at the Al-Ikhlas Orphan Boarding School, Singosari District, Malang Regency, but the power produced was not optimal. Therefore, the addition of solar modules with a capacity of 4 x 100 Wp is carried out. It is necessary to design and analyze solar power plants using pvsyst software to find out how effective the addition of solar panels is so that the total capacity is 10 x 100 Wp. This research includes the design and simulation of solar panels to optimize the system configuration, including the placement of solar panels, tilt angles, and orientation. The analysis is carried out by taking into account location data, equipment specifications, and local environmental conditions. The results of the study show that the design value of solar power plants using PVSYST software is: average annual radiation of 870 kWh/m², temperature value of 24.99°C, PV input power of 1667.2 Watts, output power of 1595.4 Watts, performance ratio of solar power plant 0.809, and efficiency value of 18.8%. After testing in the field, an average efficiency was obtained in sunny weather of 15.47% with an average voltage of 31.62 V, current of 20.03 A, and power of 651.18 Watts. The addition of solar modules significantly improves the energy production and efficiency of solar PV.